The Wizard of Oz - Baum, L. Frank; Illustrated by Granger Paul (New York Scholastic, 2012)
When a huge cyclone whisks Dorothy far away from the gray prairies of Kansas to the colorful land of Oz, it sets a courageous, determined little girl on a series of unforgettable adventures.
Including Illustrations
Keywords: Oz (Imaginary place) -- Wizard, of Oz (Fictitious character) -- Gale, Dorothy (Fictitious character)